1986
DOI: 10.1002/polb.1986.090240707
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orientation in biaxially oriented sheets of poly(ethylene terephthalate) II. Correlation of orientation averages with measured mechanical compliances

Abstract: The aggregate model is extended to examine the relationship between mechanical anisotropy and molecular orientation in one‐way drawn sheets of poly(ethylene terephthalate). It is assumed that both the aggregate and the unit of structure have orthorhombic symmetry. On the basis of a number of detailed assumptions regarding the appropriate application of the model, calculated bounds are obtained for the elastic constants that are in reasonable agreement with the experimental values. The implications of these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Since Bower developed the theory and the procedures for determining the orientation of polymer samples by polarized Raman spectroscopy in 1972, 1 several studies have been performed on PET samples. [2][3][4][5][6][7][8][9][10] These studies found that the vibrational bands 1616 and 631 cm -1 are related to the benzene ring in PET. They can provide overall molecular orientation information about the samples.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Since Bower developed the theory and the procedures for determining the orientation of polymer samples by polarized Raman spectroscopy in 1972, 1 several studies have been performed on PET samples. [2][3][4][5][6][7][8][9][10] These studies found that the vibrational bands 1616 and 631 cm -1 are related to the benzene ring in PET. They can provide overall molecular orientation information about the samples.…”
Section: Introductionmentioning
confidence: 88%
“…Among them, polarized Raman microscopy is unique in that it can provide both the second- and fourth-order Legendre polynomials, P 2 and P 4 , which describe the orientation, for particular vibrations within the samples. Since Bower developed the theory and the procedures for determining the orientation of polymer samples by polarized Raman spectroscopy in 1972, several studies have been performed on PET samples. These studies found that the vibrational bands 1616 and 631 cm -1 are related to the benzene ring in PET. They can provide overall molecular orientation information about the samples.…”
Section: Introductionmentioning
confidence: 99%
“…P 2 and P 4 are given explicitly in the theoretical section below. Since Bower developed the theory and the procedures for determining the orientation of polymer samples by polarized Raman spectroscopy in 1972, several studies have been performed on PET samples. These studies found that vibrational bands 1616 and 631 cm -1 are related to the benzene ring in PET. The 1616 cm -1 band has been assigned to the symmetric stretching of the 1,4-carbons of the benzene ring 2 and is believed to provide the average molecular orientation of the polymer chains. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Rather surprisingly, the expansion coefficient in the plane of the rings normal to the chain is larger than the value normal to the rings. The value parallel to the c axis direction is then obtained similarly from the three-dimensional equivalent of equation (1). Coupling to the amorphous phase, which would increase the apparent crystal CLTE values, was ignored.…”
Section: Crystal Phasementioning
confidence: 99%
“…In the case of biaxial film from poly(ethylene terephthalate) (PET), this has been the subject of extensive research, and much interest has focused on the resulting anisotropy in its properties (see, for example, Refs. [1][2][3][4][5][6]. Not surprisingly, poly(ethylene 2,6-naphthalate) (PEN) can be conveniently fabricated into biaxial film using the same process technology and displays a final biaxial microstructure analogous to that present in the PET case.…”
Section: Introductionmentioning
confidence: 99%